"I bet you won't": The science–society wager on gene editing techniques. (8th February 2016) - Braun, Matthias; Dabrock, Peter
Abstract : By proposing a moratorium on human germ line editing using CRISPR, scientists have entered an all‐or‐nothing wager with public opinion. A better approach would be to convene a rational and broad discussion of the fair and ethical application and regulation of gene editing and other new technologies.